Optimization of Processing Parameters for Mechanized Production of Thabdi - Kinjal Baldha; S. M. Patel; Arpita Rathva; Suneeta Pinto (Archives of Current Research International, 2024)
Present investigation has been aimed to study the effect of various processing parameters for mechanized production of Thabdi. The mechanized system based on steam jacketed kettle was used to manufacture Thabdi. Trials were conducted with different operating conditions with batch size of 6 kg milk. In research trials operation conditions were studied at steam pressure (0.8 kg/cm2, 1.5 kg/cm2, 2.0 kg/cm2) and scraper speed (15,20 and 25 rpm) for first and second stage, while (2.0 and 2.5 kg/cm2) steam pressure and (10 and 15 rpm) for last stages in mechanized kettle. Optimization of process parameters of product manufacturing was done by judging sensory attributes of final product. The sensory quality of Thabdi was found superior by adopting steam pressure 1.5 kg/cm2, scraper speed 25 rpm and batch size 6 kg during first and second stage. The third stage involved quiescent holding for fixed period of time. For the fourth stage, steam pressure 2.5 kg/cm2, scraper speed 10 rpm and batch size 6 kg were optimized for manufacture of Thabdi. In present study also compare the product manufactured under optimized conditions were compared with market sample, and it showed better results in terms of cost and sensory attributes.